#prehistoric : follow the dinosaurs - Owen, John. (New York : Scholastic, Inc., 2015)
Prehistoric animals create online profiles providing information about themselves, including what their names mean, when they lived, and how large they are.--
Iguanodon -- Trilobite -- Pterygotus -- Dunkleosteus -- Stethacanthus -- Tiktaalik -- Hylonomous -- Meganeura -- Dimetrodon -- Estemmenosuchus -- Diplocaulus -- Scutosauraus -- The Permian extinction -- Postosuchus -- Longisquama -- Desmatosuchus -- Herrerasaurus -- Morganucodon -- Tanystropheus -- Pangea -- Dimorphodon -- Stegosaurus -- Archaeopteryx -- Allosaurus -- Brachiosaurus -- Amargasaurus -- Spinosaurus -- Velociraptor -- Tylosaurus -- Elasmosaurus -- Quetzalcoatlus -- Therizinosaurus -- Parasaurolophus -- Archelon -- Pachycephalosaurus -- Pentaceratops -- Gallimimus -- Tyrannosaurus rex -- Euoplocephalus -- The K-PG extinction -- Phorusrhacid -- Titanoboa -- Icaronycteris -- Andrewsarchus -- Indricotherium -- Moropus -- Platybelodon -- Thalassocnus -- Macrauchenia -- Ceratogaulus -- Smilodon -- Woolly mammoth -- Castoroides -- Elasmotherium -- Glyptodon -- Megalania -- Gigantopithecus.
English.
Keywords: Dinosaurs -- Juvenile fiction; Dinosaurs -- Fiction; Dinosaurs; Fiction; Juvenile works